The Impact of oil rents on fiscal balance in oil dependent economies - ADEDOYIN, Fatai Festus (KDI School, 2017)
For growth prospects, many oil dependent countries prepare their budget based on revenue from sales of crude oil. A number of studies have focused extensively on the relationship between growth and deficits, however, while controlling for other variables, the research investigated oil rent’s effect on fiscal balance in the presence of fiscal rules for oil dependent economies, and for selected net oil exporting countries, while controlling for the effects of some macroeconomic, budgetary, and political variables, such as government size, interest rate, unemployment rate, inflation rate, real GDP per capita, debt-to-GDP ratio, and control of corruption. The study relied on the strengths of past studies like those of Mika Tujula and Guido Wolswijk (2004) by establishing the specific effects of oil rents for crude oil endowed economies, as one of the main determinants of fiscal balance. This establishes the importance of oil rents, amongst other previously identified macroeconomic, budgetary, and political covariates. Thus, we have attempted to overcome the shortcomings of studies that make generalized conclusions for the main determinants of fiscal balance for all countries, without highlighting specific variables that takes a huge chunk of the effects for specific natural resource endowed economies. Given large macroeconomic panel dataset, our empirical analysis solved the possibility of endogeneity, simultaneity bias and unobserved heterogeneity of oil rents and fiscal balance by the main econometric technique i.e. using an instrumental variable approach based on Dynamic Panel estimators or the General Method of Moment (GMM). This is used in comparison with estimations from pooled OLS, LSDV fixed effects, and the IV/2SLS techniques (using each country’s share of world output as instrument). Our pre-estimation diagnostics showed that the GMM approach may not be applicable to the small sample, and we suspected that the IV/2SLS method may also be weak in testing our hypothesis for the oil dependent economies with N = 20 and T = 16, and therefore we maintained the LSDV Fixed effects estimations as our main result for this category of sample countries selected. We also utilized the Drisc/Kraay standard errors, as well as the robust standard errors, which are standard errors robust to cross-sectional dependence and heteroskedasticity of unknown forms respectively, that exists in large macroeconomic panel data where N > T. Our estimation results shows that in countries with fiscal rules, there is insignificant reaction of fiscal balance to changes in oil rents shocks, and the impact is weak. We find also that welfare spending, which was captured by the real GDP per capita, affects fiscal balance, and so does the budgetary variable, i.e. debt-to-GDP ratio, and the ability of the government to curb corruption and mismanagement of funds, which is politically motivated.
Thesis(Master) --KDI School:Master of Development Policy,2017